Pengaruh Prilaku Bullying Terhadap Motivasi Belajar Siswa di Sekolah Dasar - Weni Sarbaini; Abd Aziz Tambunan (Lembag, 2025)
Education is a very well-planned way to produce a generation of young people who are intelligent, brave, and talented. However, in recent years, there have been many reports of brawls and violence committed by students in schools, indicating that humanitarian values are starting to fade. The fact that bullying often occurs in schools, which reduces students' desire to learn. According to Law No. 20 of 2003 on the National Education System, schools should create a safe learning environment and support the development of students' potential. However, the practices observed in schools actually create an unsafe atmosphere, causing students to lose interest and desire to learn. The purpose of this research is to analyze the impact of bullying behavior on the learning motivation of elementary school students and to provide solutions to this problem. The method used in this research is a Systematic Literature Review (SLR) by analyzing 10 related journals published between 2015 and 2024. Data were collected through a search on Google Scholar using the keywords